Meaning and Association - Arakelyan, Rouzanna (Armenian Folia Anglistika, 2009)
The study of associations from the perspective of psycholinguistics contributes to the comprehensive description of thinking and the types of its expression. This can be made possible through the classification of the word associations presented by the participants in the course of a psycholinguistic experiment and its analysis. As a result, it becomes clear that the type of word associations is directly linked with the perception of words and the individual nature of their application. The latter is determined by both linguistic and extralinguistic factors. Associations are the important links between ideas or between sensations that ensure the categorization of linguistic consciousness.